Antibacterial potentials of methanolic extract and silver nanoparticles from marine algae. (September 2020) - Selvaraj, P.; Neethu, E.; Rathika, P.; Jayaseeli, J. Princy Rathnamala; Jermy, B. Rabindran; AbdulAzeez, S.; Borgio, J. Francis; Dhas, T. Stalin
Abstract: Marine algae Sargassum wightii Greville ex J.Agardh and Valonopsis pachynema (G. Martens) Borgesen were collected from the coastal area of Tuticorin, Tamil Nadu and subjected to cold striping extraction and phytochemical analysis. The preliminary phytochemical analysis identified cardiac glycosides, phenolic compounds, and carbohydrates in both the algal extract, furthermore S. wightii reported to have steroids, tannins, reducing sugar and saponin. Biosynthesis of silver nanoparticles in with methanol extract of S. wightii and V. pachynema was ensured by the change of colour from yellow to dark yellowish brown color. UV–visible spectroscopy and scanning electron microscopy analysis were confirmed the formation of silver nanoparticles (AgNPs). Antibacterial activity of the algal extracts and biosynthesized AgNPs were tested against Micrococcus luteus (Gram positive bacteria) and Serratia marcescens (Gram negative bacteria). The results revealed that, 150 ppm concentration of S. wightii showed maximum antibacterial activity against M. luteus (23.33 ± 2.90 mm) and S. marcescens (14.33 ± 3.05 mm). However, 150 ppm concentration of V. pachynema recorded moderate activity against M. luteus (9.33 ± 0.33 mm) and S. marcescens (8.00 ± 0.58 mm). Whereas, among the AgNPs, 2000 ppm concentration of S. wightii and 1000 ppm concentration of V. pachynema showed maximum antibacterial activity against M. luteus and S. marcescens . In conclusion we could say that, the biosynthesized AgNPs using S. wightii has significant antibacterial potential against Gram positive (25.66 ± 0.87 mm) and Gram negative (24.33 ± 2.18 mm) bacteria. Hence, the biosynthesized AgNPs using S. wightii can be exploited for large scale studies to identify possible designing of novel antimicrobial drugs.